Silva rerum : teksty z lat 1947-1969 / Mieczysław Grydzewski ; w wyborze Jerzego B. Wójcika. - Grydzewski, Mieczysław (1894-1970) (Silva Rerum, 1994)
Felietony drukowane na łamach czasopisma "Wiadomości".